The association between sarcopenia and endotoxin in patients with alcoholic cirrhosis. Issue 36 (10th September 2021) - Sato, Shinya; Namisaki, Tadashi; Murata, Koji; Fujimoto, Yuki; Takeda, Soichi; Enomoto, Masahide; Shibamoto, Akihiko; Ishida, Koji; Ogawa, Hiroyuki; Takagi, Hirotetsu; Tsuji, Yuki; Kaya, Daisuke; et al.
Abstract : Abstract: We aimed to prospectively identify the risk factors of sarcopenia in patients with cirrhosis. Patients (n = 193) included in a discovery cohort (January 2011 and December 2014) were categorized into alcoholic (A1; n = 55) and non-alcoholic cirrhosis (NA; n = 138) groups, and those (n = 235) in a validation cohort (January 2015 to December 2019) were categorized into alcoholic (n = 92), non-alcoholic steatohepatitis-related (n = 27), and hepatitis C virus-related cirrhosis groups (n = 116). Skeletal muscle mass index (SMI) was determined using computed tomography (SMI-CT) and bioelectrical impedance analysis (SMI-BIA). Endotoxin activity (EA) was measured with an EA assay. SMI-CT correlated with grip strength in all the groups but significantly correlated with SMI-BIA of the men in group A1 ( R  = 0.64, P  < .0001) and both sexes in group NA (male: R  = 0.44, P  = .0001; female: R  = 0.35, P  = .003). SMI-CT inversely correlated with the EA levels of the men in group A1 ( R  = −0.67, P  < .0001) and myostatin levels in group NA ( R  = −0.53, P  < .0001). Lower extremity SMI had a strong negative correlation with the EA levels of the men in group A1 ( R  = −0.58, P  < .001), whereas upper extremity SMI showed an inverse trend with EA levels ( R  = −0.28, P  = .08). SMI-CT also inversely correlated with the EA levels in groups A2 ( R  = −0.52, P  = .003) and N ( R  = −0.67, P  < .0001) and myostatin levels in group C ( R  = −0.65, P  < .0001). Moreover, SMI-CT correlated with nutritional factors, including cholinesterase ( R  = 0.50, P  = .005), zinc ( R  = 0.45, P  = .01), branched amino acid-to-tyrosine ratio ( R  = 0.39, P  = .02), and triglyceride ( R  = 0.33, P  = .03) in group N. Sarcopenia risk factors differ among cirrhosis etiologies. Alcohol-induced, intestine-mediated peripheral endotoxemia could participate in sarcopenia development in patients with alcoholic cirrhosis.